Bridging the Participation Gap in Systematic Land Registration: Evaluating Legal Policy Implementation and Community Collaboration in Rural Indonesia for the Realization of Agrarian Reform - Handayani, Sri Wahyu; Kunarti, Siti; Alwan, Muhammad Dzaki; Alawiya, Nayla (Kosmik Hukum, 2026)
This study aims to analyze the implementation of the Community-Based Comprehensive Systematic Land Registration (PTSL+PM) policy and to evaluate the level of community participation in rural Indonesia.This study employs a mixed-methods approach with a socio-legal perspective integrating qualitative and quantitative analyses. Data were collected through field observations, in-depth interviews, Focus Group Discussions (FGDs), and questionnaires administered to 97 respondents in Samudra Kulon Village.Analysis was conducted using a theoretical framework of community participation and legal implementation to assess participation levels and policy effectiveness.The findings indicate that the implementation of the PTSL+PM program has proceeded in accordance with established procedures during the planning stage but has not been optimal during the physical and legal data collection stages due to technical and social constraints.The level of community participation falls into the high category, with an index of 2.81, reflecting a collaborative pattern between the government and the community.Nevertheless, this participation remains largely procedural and is not yet fully substantive, indicating the presence of a participation gap. This study concludes that the success of land registration policy implementation is determined not only by the regulatory framework but also by the quality of community participation and the associated social dynamics. Therefore, strengthening participatory mechanisms, enhancing the capacity of local institutions, and improving policy communication are necessary to increase the effectiveness of the PTSL program.